The potential impact of iron supply on the development of starved Enterococcus faecalis biofilm by modulating the liberation of extracellular DNA - Zhen, Yuqi; Baima, Quzhen; Yang, Shipeng; Cao, Yu; Meng, XiuPing (Frontiers in Microbiology, 2025)
Enterococcus faecalis (E. faecalis) is commonly associated with persistent periapical infections. Even after multiple courses of root canal therapy, the infection is difficult to eradicate due to its drug resistance and adaptability. However, root canal treatment will remove nutrients from the root canal and make the remaining E. faecalis near starvation. Iron is an essential element for the growth and metabolism of E. faecalis, but previous studies were mostly based on bacterial nutrient sufficient conditions. Therefore, in this study, the starvation state was used as the breakthrough point to explore the mechanism of iron on the biofilm formation of E. faecalis, so as to be more suitable for clinical practice. In this study, we first constructed a starving E. faecalis model. Subsequently, we found that iron supply promoted biofilm formation in starved E. faecalis, with more eDNA in the biofilm. Iron starvation induced by the iron competitive inhibitor gallium nitrate reduced biofilm formation but increased the proportion of eDNA. In contrast, high iron levels in the environment counteracted this inhibition of biofilm formation. Following DNase I treatment, both the eDNA content and viable bacteria within the biofilm of the iron-supply group exhibited a statistically significant reduction. These results suggest that iron supply may regulate the proliferation of active bacteria by regulating eDNA release, thereby promoting biofilm formation of starved E. faecalis and providing a new perspective on its survival strategy under stress.